Palatal approach of anterior superior alveolar injection technique may not be potentially useful in periodontal procedures - Pragathi Raghavendra Bhat; Anirudh Balakrishna Acharya; Srinath Lakshman Thakur (Wolters Kluwer Medknow Publications, 2016)
Background: The palatal approach of anterior superior alveolar (P-ASA) using WAND injection was reported to effectively provide a profound bilateral maxillary anesthesia of the soft tissue of anterior one-third of the palate and facial gingivae extending from canine to canine which lasted for more than an hour thus making it ideal for scaling root planing and minor periodontal procedures in the anterior maxilla. Our study suggests that the conventional P-ASA injection is of very short duration and the extent of anesthesia was not profound and consistent. This has not been reported earlier in the literature. Materials and Methods: Thirty-five cases (20 males and 15 females), who underwent scaling, root planing and minor periodontal surgical procedures such as abscess drainage, gingivectomy, and frenectomy in the maxillary anterior region in the age range of 19-45 years was assessed for the efficacy of the P-ASA injection. After the administration of the P-ASA injection, the subjective and the objective symptoms were used to evaluate the extent and duration of the anesthesia at 10, 15, and 20 min. Results: This study suggests that the conventional P-ASA injection technique does not provide anesthesia for more than 20 min. Wilcoxon matched pairs test was used to compare the effect of anesthesia at the different time intervals and the results were found to be statistically significant (P < 0.05). Conclusions: The conventional P-ASA injection technique is of very short duration and does not demonstrate effectiveness in periodontal surgery of the anterior maxilla.